KRITIK NETIZEN TERHADAP OTORITAS KYAI DALAM LIPUTAN TRANS7: ANALISIS WACANA TIKTOK BERDASARKAN TEORI RELASI KUASA MICHEL FOUCAULT - Abdurrahman Afif; Ahmad Ridwan; Refti Handini; Fransiscus Xaverius Sri Sadewo (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2026)
This study examines the virality of criticism of the authority of Islamic scholars (kyai) in a Trans7 report widely discussed on TikTok, and how power and gender relations in the context of Islamic boarding schools (pesantren) are reproduced and negotiated through digital discourse. Drawing on Michel Foucault's theory of power relations, this study aims to understand how religious authority is constructed, maintained, and questioned through public interactions on social media. The study uses a qualitative approach with Norman Fairclough's Critical Discourse Analysis method, with data consisting of one TikTok video containing the report and four purposively selected netizen comments as the primary units of analysis. The results show that netizen criticism functions as a counter-discourse that challenges the traditional construction of Islamic boarding school (kyai) authority, particularly on issues of abuse of power, lack of accountability in Islamic boarding schools (pesantren) institutions, and gender inequality. The virality of TikTok plays a significant role in expanding the reach of criticism, creating a participatory space that allows the public to intervene in religious narratives previously dominated by Islamic boarding school authorities. These findings confirm that the digital space has shifted the relationship between Islamic boarding school (kyai) and santri and opened up new mechanisms for the public to evaluate religious practices. This research contributes to the sociology of religion by demonstrating that power relations are no longer static but are continually negotiated through digital discourse. The implications of these findings emphasize the importance of careful production and regulation of religious content on social media, as well as the need to develop a more contextual analytical framework to understand the dynamics of power relations in Indonesian Islamic society.